Determinants of members loyalty towards cooperative in Sarawak / Syed Muhammad Othman Sayed Hussein - Sayed Hussein, Syed Muhammad Othman (2016)
This research attempts a quantitative investigation that measure and identify the determinants of member’s loyalty towards cooperative in Sarawak. There are so many determinants of member’s loyalty, but this research was only focusing on four determinants of member’s loyalty which are satisfaction, trust, value and resistance to change. Although, the previous research had emphasized on discussion towards loyalty but it is lack of study towards on the determinants towards members loyalty among cooperative. This research will describes an empirical studies to find the significant relationship and also the strength of the relationship between member’s loyalty towards satisfaction, trust, value and resistance to change. A survey had been conducted in non probability sampling technique which was convenience method by selecting cooperative training institution, MaktabKoperasi Malaysia (MKM) Sarawak, that representing Cooperative Members in Sarawak. This study used descriptive methods to describe the behavior of data and Statistical Package for Social Science (SPSS) version 22 was used to analyze the data collected. Summaries of reasons and discussions of the finding for each research question are also given. This findings give some thought on the better understandings of determinants of member’s loyalty towards cooperative. Cooperative may find these result very helpful to improve their member’s loyalty and remain competitive in business organization competition to achieve their goals.